(untitled) (EAAE Annual Conference Proceedings, 2025)
Architecture as a discipline and drawing as it’s primary craft are often considered as a solution-providers, offering stable responses to spatial demands. These ‘architectural solutions’ are highly conditioned by the building industry’s quests for speed, financial efficiency and investor’s benefice. This common practice is resulting in simplifying the overall capacity of architectural creative thinking and doing. Can we use the unstable state of drawing as critical agency for asking questions instead of providing solutions? Here presented approach suggests the design research domain as a field of action towards the ethical and mindful architecture. This paper elaborates on the design-driven research processes within the educational context of the second year of Master studies at the Faculty of architecture, University of Belgrade (2024/25).1 The inquiry is founded on the methodology of liminal drawing (2) and related experiment in the teaching course Tactics of the design-driven research. Bnin-Bninski defines liminal state of drawing based on the notion of preliminary (3) as a design research critical tactic confronted to the long-term established routines and procedures in the architectural design. The starting premises for this course include the awareness and emphatic relation between the spaces we inhabit and the spaces we project.4 The discussed results are the individual student works of hanging mobile structures (strings and folded paper) of spatial segments arranged in the unstable state of relational constellations. 1. Anđelka Bnin-Bninski. “Tactics of the design-driven research.” 2. Anđelka Bnin-Bninski. “The role of architectural drawing in the dynamics of living space partition.” 3. Andrew Benjamin. “The Preliminary: Notes on the Force of Drawing.” 4. Claus Pedersen et al., eds., CA2RE+: Strategies of design-driven research.